2014
DOI: 10.1242/jeb.103093
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of BK channel expression is sufficient to alter auditory hair cell thresholds in larval zebrafish

Abstract: Non-mammalian vertebrates rely on electrical resonance for frequency tuning in auditory hair cells. A key component of the resonance exhibited by these cells is an outward calcium-activated potassium current that flows through large-conductance calciumactivated potassium (BK) channels. Previous work in midshipman fish (Porichthys notatus) has shown that BK expression correlates with seasonal changes in hearing sensitivity and that pharmacologically blocking these channels replicates the natural decreases in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The first step has now been made in furthering our understanding of the ability of BK channel expression changes to shape auditory tuning by targeting slo1 gene expression in larval zebrafish. Consistent with the midshipman work [119], reduction of BK channel expression via use of morpholinos results in higher saccular thresholds than controls [120]. …”
Section: Seasonal Enhancement Of Hearingsupporting
confidence: 79%
“…The first step has now been made in furthering our understanding of the ability of BK channel expression changes to shape auditory tuning by targeting slo1 gene expression in larval zebrafish. Consistent with the midshipman work [119], reduction of BK channel expression via use of morpholinos results in higher saccular thresholds than controls [120]. …”
Section: Seasonal Enhancement Of Hearingsupporting
confidence: 79%
“…Among the ion channels upregulated in reproductive SE were large conductance, calcium-activated potassium (BK) channel transcripts (Table 5 , Additional file 2 ) that have been localized to saccular hair cells in midshipman, shown to vary in abundance across seasons and to regulate auditory sensitivity in midshipman adults and zebrafish larvae [ 12 , 61 ]. Numerous other potassium channel transcripts were also differentially regulated across seasons (Additional file 2 ), which may be necessary for the fine-tuning of auditory thresholds, as demonstrated in other vertebrates [ 62 ] and suggested by our auditory physiology studies of the SE [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is unknown whether this pathway is developed in larval zebrafish, as most studies of hearing in zebrafish have looked at juveniles or adults (Cervi, Poling, & Higgs, ; Higgs et al, ; Higgs, Souza, Wilkins, Presson, & Popper, ; Mueller, ; Wang et al, ). The few studies assessing larval hearing have used microphonic potentials to gauge responses in the ears' hair cells (Lu & DeSmidt, ; Rohmann, Tripp, Genova, & Bass, ; Yao et al, ), and this work has shown responses to tones ranging from 20 Hz to 400 Hz as early as 3 days postfertilization (dpf) (Yao et al, ). By 5–6 dpf, larvae startle to tones up to 1,000 Hz, although these responses require extremely strong stimuli (Bhandiwad, Zeddies, Raible, Rubel, & Sisneros, ).…”
Section: Introductionmentioning
confidence: 99%